Potential reproductive impairment due to Solanum glaucophyllum-induced calcinosis in female ruminants - Garcia, Juan Agustin; Rodriguez, Alejandro; Scioli, Maria Valeria; Azaldegui, Ignacio; Tiberio, Agustin; Pachiani, Martina; Vilatuña Lita, Elvis; Sosa, Emiliano; Canton, German Jose (Springer, 2025)
Solanum glaucophyllum is a toxic calcinogenic plant endemic to Central Argentina and is widely recognized as the primary cause of enzootic calcinosis in ruminants. Although the systemic calcification induced by this plant is well documented, its potential impact on reproductive performance remains underexplored. The present study reports the first evidence of calcinosis affecting the female reproductive organs of ruminants. Reproductive tissues-including the uterus, ovary, and oviduct-were obtained from a non-pregnant 4-year-old Texel ewe and a 6-year-old Hereford cow that exhibited gross signs of systemic calcification following S. glaucophyllum ingestion. Histopathological examination revealed extensive granular basophilic calcium deposits within the tunica media and/or intima of blood vessels in these organs, accompanied by varying degrees of non-mineralized hyperplasia. The deposits were confirmed as calcium by Von Kossa staining. These findings suggest that vascular calcification in reproductive tissues may reduce blood flow, thereby impairing the delivery of hormones essential for follicular growth, ovulation, fertilization, and embryo implantation. Given that subclinical calcinosis may compromise reproductive efficiency, this phenomenon could have significant economic repercussions for the livestock industry. Further investigations are warranted to quantitatively assess the degree of calcification, vascular perfusion, and additional reproductive parameters to elucidate the impact of S. glaucophyllum-induced calcinosis on fertility.